2015
DOI: 10.3233/jad-150088
|View full text |Cite
|
Sign up to set email alerts
|

The 5XFAD Mouse Model of Alzheimer’s Disease Exhibits an Age-Dependent Increase in Anti-Ceramide IgG and Exogenous Administration of Ceramide Further Increases Anti-Ceramide Titers and Amyloid Plaque Burden

Abstract: We present evidence that 5XFAD Alzheimer's disease model mice develop an age-dependent increase in antibodies against ceramide, suggesting involvement of autoimmunity against ceramide in Alzheimer's disease pathology. To test this, we increased serum anti-ceramide IgG (2-fold) by ceramide administration and analyzed amyloid plaque formation in 5XFAD mice. There were no differences in soluble or total amyloid-β levels. However, females receiving ceramide had increased plaque burden (number, area, and size) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 36 publications
3
55
1
Order By: Relevance
“…The ThioS-positive plaque burden in 14-week female 5XFAD was found to be ~0.7% (calculated from the data in [43]) and the burden of plaques stained with X-34, another stain for fibrillar Aβ, in 4-month mice (gender unspecified) was ~0.8% [9], close to the 0.5% ThioS burden that we found in 3-month female 5XFAD mice. In 6-month 5XFAD mice (both males and females used in this study), the ThioS burden has been reported as 2.5–3% [44], similar to the 3.6% that we found in 6–9-month female mice.…”
Section: Discussionsupporting
confidence: 71%
“…The ThioS-positive plaque burden in 14-week female 5XFAD was found to be ~0.7% (calculated from the data in [43]) and the burden of plaques stained with X-34, another stain for fibrillar Aβ, in 4-month mice (gender unspecified) was ~0.8% [9], close to the 0.5% ThioS burden that we found in 3-month female 5XFAD mice. In 6-month 5XFAD mice (both males and females used in this study), the ThioS burden has been reported as 2.5–3% [44], similar to the 3.6% that we found in 6–9-month female mice.…”
Section: Discussionsupporting
confidence: 71%
“…However, females with AD generally have more neuropathology and cognitive impairment than males, and neuropathology has a stronger relationship with symptomology and disease diagnosis in females than males . In 5xFAD mice, females also show more AD‐related pathology than males, including increased Aβ‐plaque load, and elevated levels of APP and Aβ‐42 as early as 4‐6 months of age (Sadleir et al, 2015) . These sex differences cannot simply be attributed to differences in transgene expression, given similar levels of hAPP and hPS1 mRNA have been observed in male and female 5xFAD mice …”
Section: Discussionmentioning
confidence: 99%
“…48 In 5xFAD mice, females also show more ADrelated pathology than males, including increased Aβ-plaque load, 33,34 and elevated levels of APP and Aβ-42 as early as 4-6 months of age (Sadleir et al, 2015). 31 These sex differences cannot simply be attributed to differences in transgene expression, given similar levels of hAPP and hPS1 mRNA have been observed in male and female 5xFAD mice. 49 Previous studies documenting motor dysfunction in 5xFAD mice have used only one sex of 5xFAD mice, 22,24 and this is the first study to examine sex differences in motor impairments.…”
Section: Are There Sex Differences In the Progression Of The Motor mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroblastoma-derived exosomes injected into an AD-model mouse brain were shown to take up Aβ and reduce Aβ levels, amyloid depositions, as well as Aβ-mediated synaptotoxicity in the hippocampus (Yuyama et al 2014, Yuyama et al 2015). In contrast, an increase in serum exosome levels correlated with an enhanced amyloid plaques in the brains of the 5XFAD mouse model of AD (Dinkins et al 2015). In additon, reducing exosome secretion by the nSMase2 inhibitor GW4869 resulted in a diminished amount of amyloid plaques in the same mouse model (Dinkins et al 2014).…”
Section: Discussionmentioning
confidence: 99%